Reclamation and Beneficial Use of Contaminated Dredged Material: Implementation Guidance for Select Options. - Lee, Charles R. (2000)
The purpose of this technical note is to provide implementation guidance for select options for the reclamation and beneficial use of contaminated dredged material. Previous technical notes have discussed the characterization tests that can provide information necessary to assist in the determination of the suitability of dredged material for beneficial uses and the application of these characterization tests to case studies of beneficial uses of dredged material. This technical note will build on the previous technical notes and give perspective to their implementation. Beneficial use of dredged material is not a new concept. For years, relatively clean dredged material has been used for numerous beneficial uses. Beneficial uses of dredged material have been discussed in many forums such as the North Atlantic Regional Conference in 1987 (Landin 1988). Engineer Manual (EM) 1110-2-5026 (Headquarters, U.S. Army Corps of Engineers, 1987) discusses numerous beneficial uses of dredged material from aquatic, island, wetland, and upland habitat to strip-mine reclamation and construction and industrial/commercial uses. Most of the sites discussed have used relatively clean dredged material containing low levels of contaminants. Guidelines for disposal area reuse (DARM) have been discussed by Montgomery et al. (1979). Planning and implementing productive land use of dredged material containment areas was discussed by Walsh and Malkasian (1978). Guidance for land improvement using dredged material was published as a synthesis report by Spaine, Llopis, and Perrier (1978).